Risk assessment factors for SME software development companies in Malaysia - Sharif, A.M. (Institute of Electrical and Electronics Engineers Inc., 2014)
There are large, medium, and small enterprises which develop software projects that can be influenced by a risk. Identifying risk is first step of perfectly assessing and controlling risks in a project. In the literature, a lot of researchers identified risk factors in software projects but none of these can be generalized as base of risk factors in the software projects as they differ in time, culture, and being studied in different application areas while using different research methodologies. Majority of the researchers focused on general software projects while few of them focused on specific application areas like virtual projects or e-commerce projects but no research focused identifying risk factors of software projects in terms of the firm size. In this paper, we are studying risk factors that Small and Medium Enterprise (SME) in Malaysia perceive as risk in their software development projects. 202 respondents from 25 enterprises located in three states in Malaysia was surveyed and analyzed. Finally, the top risk factors for each risk dimension were presented along their relationship with project risks. Â© 2014 IEEE.